Studies on the biology of the scads, Decapterus russelli and Decapterus macrosoma at Vizhinjam, southwest coast of India - Balasubrahmanian, N K; Natarajan, P (Indian Journal of Fisheries, 2011)
Predominant among carangids, the scads Decapterus russelli and Decapterusmacrosoma, though showed female domination, did not show any significantdivergence in sex ratio. Both the species were found to breed continuously withtwo peak spawning seasons. While March to May and November to Decemberwere the periods for D. russelli, the same were between February, June, Octoberand December in D. macrosoma. When D. russelli males and females attainedfirst maturity at age 0.91 years (150 and 140 mm total length respectively), D.macrosoma species attained maturity on reaching 1.05 years (male 158 mm andfemales 157 mm). The regression coefficient and Y-intercept of the logarithmiclength-weight relationship were 2.9251; -1.8668 and 3.46231; -3.1139 respectivelyfor D. russelli and D. macrosoma. The ELEFAN analysis showed L